Sociological context in Spanish high level athletics by gender - Vidal, A. M.; Padorno, C. M.; Polifrone, M.; Patino, M. J. M. (Journal of Human Sport & Exercise, 2010)
This research analyzes different aspects related to the sociological context of Spanish sportsmen and sportswomen, specifically the sociological context of athletics, in a time when women practically compete in the same events than men, and sports are accessible and desirable for them. A questionnaire was carried out among the athletes to obtain information about the social aspects, the preferences and the degree of satisfaction of their condition as athletes on one hand, and the presence or the feelings about different treatment between the two sexes on the other. The data have been then analyzed statistically as a fundamental tool of the methodology used in this survey. The study confirms that women have succeeded in establishing a position of equality with men for number of participants at high competitions and for the level of performance.